Organizational models in the fact-checking media: Comparative analyisis of The Fact Checker and Maldita.es - Andaluz Antón, Lucía; Fernández Fernández, Ángel; Pérez Sánchez, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper analyzes the organizational models most commonly used in media dedicated to fact-cheking, taking as a reference the classification made by Graves and Cherubini (2016). It distinguishes between the so-called Newsroom model and the NGO model, which respectively correspond to projects included in the functional structure of another media and to projects, often non-profit, that develop their activity independently. For this purpose, a comparative analysis is made of The Fact Checker and Maldita.es, two consolidated projects that exemplify the most relevant characteristics of each of these models.